Satyagraha and employee relations: Lessons from a multinational automobile transplant in India - Kunju Kunju Mathew, Sagi; Jones, Robert (Emerald, 2012)
Purpose – The purpose of this paper is to analyse the role of non-violent protest (satyagraha) in a multinational automobile plant in India that has suffered from considerable employee relations problems. Design/methodology/approach – The paper employs a case study of a Japanese-owned company using data obtained from 30 personal interviews and from internet media sources. Findings – It is found that workers initially pursued their protests through satyagraha-style methods before taking on a more violent posture when company management refused to accept any notion of jointly seeking a new harmony. The reasons for these developments are explored. Practical implications – The paper has implications for the manner in which scholars and practitioners view the respective roles, significance, and management of satyagraha and non-satyagraha protest in Indian companies. Originality/value – The importance of satyagraha in Indian employee relations is under-researched in comparison with other factors, and is especially significant for culturally-unaware multinational companies in successfully understanding and managing protest in the workplace context.